2016
DOI: 10.1142/s0217751x16501293
|View full text |Cite
|
Sign up to set email alerts
|

Quantum gravity effects on charged microblack holes thermodynamics

Abstract: The charged black hole thermodynamics is corrected in terms of the quantum gravity effects. Most of the quantum gravity theories support the idea that near the Planck scale, the standard Heisenberg uncertainty principle should be reformulated by the so-called Generalized Uncertainty Principle (GUP) which provides a perturbation framework to perform required modifications of the black hole quantities. In this paper, we consider the effects of the minimal length and maximal momentum as GUP type I and the minimal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 75 publications
2
11
0
Order By: Relevance
“…It is also shown that the minimum mass and its order of magnitude increase and the temperature peak shift to lower temperature when the electric charge increases ( Figure 6). It is in full agreement with the results of previous manuscript of authors [56]. We have shown that the charge variation is more effective on the temperature compared to the angular momentum variation (see Figure 7).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is also shown that the minimum mass and its order of magnitude increase and the temperature peak shift to lower temperature when the electric charge increases ( Figure 6). It is in full agreement with the results of previous manuscript of authors [56]. We have shown that the charge variation is more effective on the temperature compared to the angular momentum variation (see Figure 7).…”
Section: Resultssupporting
confidence: 93%
“…[31] due to the line element dependency to gauge charge compared to the proposed solution in [54]. Although it was shown [55] that the TeV-scale black hole charge will reach zero much faster than its mass and the charge to mass ratio is much less than one [56], we have shown here that charge is more effective on Hawking temperature variation compared to the angular momentum in fixed mass (see Figure 7). Therefore, if the fundamental Planck scale is of the order of TeV, the Large Hadron Collider would produce charged rotating micro black hole which as a consequence of their evaporation, degenerate to charged non-rotating TeVscale balck hole at the last stage and thus yield charged black hole remnants.…”
Section: Effects Of Angular Momentum and Charge On Thermodynamicsmentioning
confidence: 59%
“…(8) returns to the Lorentz model. But here we would like to discuss another interesting case where n is not always equal to 1, as the general Lorentz violating models suggested [1][2][3][4][5][6].…”
Section: Particle's "Maximum Energy"mentioning
confidence: 99%
“…It is well known that the Special Relativity and General Relativity, which are proposed based on the Lorentz invariance, have already made great achievements, but at the same time the Lorentz violating models are also of some astrophysical interest. In the past few decades, the Lorentz violating models have been proposed in various frameworks and theories of Quantum Gravity, such as the string theory [1][2][3], the loop quantum theory [4,5], and the non-commutative time-space theory [6], which aim to combine the Quantum theory and the gravity theory. In many models called "Quantum Gravity", the "minimum length" or "maximum energy" independent of the inertial systems, is assumed, which imply the Lorentz invariance is violated in the ultrahigh energy scale.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the Special Relativity and General Relativity, implying the Lorentz invariance, have already made great achievements, but at the same time the Lorentz violating models are also of some astrophysical interest. In the past few decades the scientific community has shown an intense interest in the theories that contained and investigated the breakdown of Lorentz symmetry in many scenarios [1][2][3][4][5] and also the so-called Deformed Special Relativities (DSR) [6]. For example, in this scenario of considering the combination of Quantum theory and Gravity theory, the rainbow model is proposed, which introduces the "minimum length" as another constant between inertial systems besides the speed of light.…”
Section: Introductionmentioning
confidence: 99%